Kinematic Analysis of A Front Flip Pike on A Mini Trampoline - Ahmed Qasim Kadhim (Indonesian Journal Publisher, 2025)
The aim of this study was to investigate the linear kinematics of the a front flip pike on a mini trampoline. The study sample was one player In this study, a high-speed digital video camera was used, set to 120 frames per second, and the linear kinematic data were calculated using the Kinovea software. The variables were calculated in six phases. Increase in the horizontal velocity and decrease in the vertical velocity in the contact phase. Increase in the vertical velocity and decrease in the horizontal velocity in the take off phase. Decrease in the displacement values ​​on the horizontal axis and increase in the vertical axis in the rise phase. A significant increase on the horizontal level accompanied by a velocity of the center of mass on the same axis with a continued increase in the displacement values Vertical and decrease in velocity values. In the landing phase, the horizontal displacement continues to increase and the vertical displacement values ​​decrease. It is suggested that players improve to increase the vertical velocity in the take off phase and train to control the limbs perfectly in the air